How should we choose the 'best' embryo? A commentary on behalf of the British Fertility Society and the Association of Clinical Embryologists. (3rd July 2015) - Bolton, Virginia N.; Leary, Christine; Harbottle, Stephen; Cutting, Rachel; Harper, Joyce C
Abstract: Embryo selection to improve pregnancy rates remains a significant challenge in IVF. Non-invasive and invasive methods of embryo selection include morphological assessment, metabolomics, time-lapse imaging and preimplantation genetic screening. To date, none has been shown conclusively to yield improved implantation and live birth rates. This review summarises current understanding of methods for embryo selection.